Status of the WHO recommended timing and frequency of antenatal care visits in Northern Bangladesh - Sarker, Bidhan Krishna; Rahman, Musfikur; Rahman, Tanjina; Rahman, Tawhidur; Khalil, Jubaida Jahan; Hasan, Mehedi; Rahman, Fariya; Ahmed, Anisuddin; Mitra, Dipak Kumar; Mridha, Malay Kanti; Rahman, Anisur (PLOS ONE, 2022)
This article was published in PLOS ONE by BMJ Journals [© 2020 Sarker et al. This is an open access article distributed under the terms of the Creative Commons Attribution License,] and the definite version is available at: https://doi.org/10.1371/journal.pone.0241185 The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0241185